IDENTIFIKASI BAKTERI PADA SERASAH DAUN MANGROVE YANG TERDEKOMPOSISI DI BANDAR BAKAU KOTA DUMAI - Putri Wening Ratrinia; Nirmala Efri Hasibuan; Aulia Azka; Sumartini Sumartini; Apri Mujiyanti; Kurnia Sada Harahap; Muh Suryono (JURNAL PERIKANAN TROPIS, 2020)
Bacteria has an important role in decomposition and productivity activities in mangrove ecosystem. The study about identification of decomposing mangrove litter bacteria in Dumai has never been done. The aim of this study is to determine Total Plate Count and identify the dominant bacterial species from decomposing Rizhopora sp, Xylocarpus sp, dan Avicennia sp litter in Dumai. The method used in this research was survey method, bacterial isolation was done by pour plate method which is used in total calculation of bacteria was Total Plate Count (TPC), and identify the dominant bacterial in mangrove litter. The total bacteria which gained on Avicennia sp leaf litter are 0,64 x 105 Cfu/ml. On the other hand, the total bacteria from Rhizopora sp leaf litter has a lower number of colonies that is 0,55 x 105± 0,01 Cfu/ml. The bacterial identification test was carried out by gram staining method and morphological observation by microscopy. The dominant bacterial species in three mangrove species (Rizhopora sp, Xylocarpus sp, dan Avicennia sp) are Micrococcus sp dan Aerococcus sp. Keywords : Total Plate Count, Micrococcus sp, Aerococcus sp, Organic Matterial